Computed Tomographic Findings and Clinical Manifestations of Acute Severe Hypersensitivity to a Non-Ionic Iodinated Contrast Agent in a Castrated Male Dog: A Case Report - Minsoo Chung; Jungmin Kwak; Kidong Eom; Jaehwan Kim (Animals, 2026)
Severe adverse reactions induced by non-ionic contrast media remain an uncommon complication in veterinary medicine. This report describes the clinical manifestations and sequential computed tomography alterations indicative of acute shock captured during 2 min and 4 min delayed phases in a 10-year-old, castrated male Maltese dog. The patient, previously diagnosed with a cutaneous mast cell tumor on the lip exhibiting incomplete histopathological margins, underwent CT for metastatic evaluation. The patient had no clinical evidence of systemic disease, and no anesthetic adverse events were observed during past patellar luxation surgery. However, the 2 min delayed CT scan revealed suspected hepatic congestion, vascular collapse, marked esophageal wall edema, and intense intestinal mucosal contrast enhancement. Subsequently, the 4 min delayed CT scan demonstrated diffuse contrast medium stagnation within the cardiac chambers and renal parenchyma, accompanied by the absence of the renal excretory phase. During anesthetic recovery, severe hypotension and respiratory failure emerged, suggesting the development of hypersensitivity. Following immediate intervention with cardiopulmonary resuscitation, epinephrine, and dexamethasone, the patient temporarily exhibited facial edema, hematochezia, diarrhea, and transient ataxia. However, dobutamine administration successfully restored systemic blood pressure and tissue perfusion, returning the patient to a normal clinical status. Consequently, this case highlights potential pathophysiological mechanisms, key CT findings, and emergency management considerations for contrast-induced hypersensitivity. Notably, sequential CT imaging documented evolving shock-related changes before the onset of overt clinical deterioration, suggesting that these findings may represent early imaging indicators of contrast-induced hypersensitivity.